Frekuensi menggunakan aplikasi delivery food dan indeks massa tubuh (IMT) pada mahasiswa Poltekkes Bengkulu - Niken Shovianti; Betty Yosephin Simanjuntak; Yenni Okfrianti (Poltekkes Kemenkes Aceh, 2024)
Background: Food delivery applications are increasingly popular among students, providing convenience in ordering food that is often high in energy, potentially affecting Body Mass Index (BMI).Objective: To explore the relationship between the frequency of using food delivery applications and BMI among students at Nutrition Deparment Poltekkes Kemenkes Bengkulu.Method: This observational analytic study employed a cross-sectional design, involving 64 students from the Nutrition Department aged 18-24 who had food delivery applications. Data were collected in May 2024 through interviews regarding the frequency of app usage and direct anthropometric measurements for BMIResults: Among the 64 students, 24 used the application 1-3 times a week, with 15 exhibiting abnormal nutritional status. Additionally, 12 students used the app more than 3 times a week, of which 8 (66.7%) had abnormal nutritional status. A significant relationship was found between the frequency of app usage and BMI (p=0.001; OR 3.492)Conclusion: The frequency of using food delivery applications is linked to nutritional issues, particularly BMI. Students with low BMI are encouraged to improve their nutritional intake, while those with high BMI should manage their diet and increase physical activity.